External imbalances and the US current account: how supply-side changes affect an exchange rate adjustment - Philipp Engler; Michael Fidora; Christian Thimann (European Central Bank (ECB), 2007)
The influential work of Obstfeld and Rogoff argues that a closing-up of the US current account deficit involves a large exchange rate adjustment. However, the Obstfeld-Rogoff model works exclusively via demand-side channels and abstracts from possible supply-side changes. We extend the framework to allow for endogenous supply-side changes and show that this fundamentally alters the mechanism of the adjustment process. Allowing for such an extension attenuates quite significantly the implied exchange rate adjustment. The paper also provides some empirical evidence of variations in the supply-side structure and correlations with the exchange rate and the current account. The policy implications are that measures to foster a supply-side reaction would facilitate the external adjustment by alleviating an exclusive reliance on demand and exchange rate changes, with the latter being potentially destabilising for the global financial system.
Keywords: E2; F32; F41; 330; dollar adjustment; global imbalances; sectoral adjustment; US current account deficit; Außenwirtschaftliches Gleichgewicht; Leistungsbilanz; Wechselkurs; USA